Genome-wide identification and expression profiles analysis of the authentic response regulator gene family in licorice - Shi, Yanping; Ding, Guohua; Shen, Haitao; Li, Zihan; Li, Hongbin; Xiao, Guanghui (Frontiers in Plant Science, 2024)
Introduction As one of the traditional Chinese medicinal herbs that were most generally used, licorice attracts lots of interest due to its therapeutic potential. Authentic response regulators (ARRs) are key factors in cytokinin signal transduction and crucial for plant growth and stress response processes. Nevertheless, the characteristics and functions of the licorice ARR genes are still unknown. Results In present study, a systematic genome-wide identification and expression analysis of the licorice ARR gene family were conducted and 51 ARR members were identified. Collinearity analysis revealed the significant roles of segmental duplications in the expansion of licorice ARR genes. The cis-acting elements associated with development, stress and phytohormone responses were identified, implying their pivotal roles in diverse regulatory processes. RNA-seq and qRT-PCR results suggested that A-type, but not B-type ARRs were induced by zeatin. Additionally, ARRs participated in diverse abiotic stresses and phytohormones responses. Yeast one-hybrid assay demonstrated that GuARR1, GuARR2, GuARR11, GuARR12, GuARR10-1, GuARR10-2 and GuARR14 were able to bind to the promoter of GuARR8-3, and GuARR1, GuARR12 bound to the GuARR8-1 promoter. GuARR1, GuARR2, GuARR11 and GuARR10-2 bound to the GuARR6-2 promoter as well as GuARR12 and GuARR10-2 bound to the GuARR6-1 promoter. Discussion Collectively, these findings provide a basis for future ARR genes function investigations, shedding light on the potential medicinal properties and agricultural applications of licorice.